(untitled) (Indian Journal of Arid Horticulture, 2025)
Punjab, contributing 35-40% of rice and 40-70% of wheat to the central pool, has a high cropping intensity (196-200%). This study evaluates the economic impact of integrating short-duration summer vegetables with major cropping systems. Survey data revealed that paddy-potato crop rotation recorded the highest net returns (Rs.1,18,467/acre), whereas paddy-wheat had the highest B:C (2.71). Inclusion of summer vegetables significantly increased economic indices like net returns and B:C in paddy-wheat by 84.87 and 4.06 per cent, and in paddy-mustard by 126.23 and 21.46 per cent, respectively. Cultivation of summer vegetables enhanced the land use efficiency from 71.23 to 95.89 per cent in case of paddy-wheat crop rotation. Summer vegetable cultivation increased land use efficiency from 68.49 to 93.15 per cent in paddy-mustard cropping system. Inclusion of summer vegetables significantly enhanced the system productivity of all the existing crop rotations. In paddy-wheat rotation an increase in system productivity by about 179.96 per cent was recorded due to cultivation of summer vegetables. Results of the study clearly show immense potential of short duration summer vegetables in enhancing the farm profitability and sustainability while justifying the objectives of crop diversification in Punjab state.